Interpreting Moderate Islam in Indonesian Digital Media: A Critical Discourse Analysis of Islami.co and IBTimes.id - Ahmad Aminuddin (Journal of Education and Religious Studies, 2024)
The rapid growth of digital media has reshaped Islamic discourse in Indonesia, becoming a key space for promoting and contesting narratives such as Moderate Islamic understanding (wasathiyah). This study uses a qualitative approach to analyse how Islamic digital platforms, Islami.co and IBTimes.id, construct and disseminate moderate Islamic discourse through Quranic interpretation and narrative strategies. The study uses Norman Fairclough’s Critical Discourse Analysis (CDA) to examine four selected articles interpreting key verses like QS Al-Baqarah 2:143 and QS Al-Imran 3:104. Findings reveal that while both platforms promote inclusive and anti-extremist views, they differ in theological framing and sociocultural orientation. Islami.co emphasizes classical exegesis with contextual storytelling, portraying moderation as moral balance and personal piety. Meanwhile, IBTimes.id frames moderation in civic and political terms, linking it to national unity and global diplomacy. Both platforms sacralize Pancasila by linking it with Quranic principles, reinforcing narratives aligned with national identity. Their digital strategies, such as content structuring and SEO optimisation, often align with the perspectives of dominant Islamic institutions like NU and Muhammadiyah. Despite youth involvement, both platforms tend to reproduce existing institutional norms. This study reveals that theological interpretations and broader socio-political dynamics and communication practices shape moderate Islamic moderation understanding in digital media and affirms how scripture, politics, and media converge in shaping contemporary Islamic identities in Indonesia.